Nesfatin-1 ameliorates oxidative bowel injury in rats with necrotizing enterocolitis: The role of the microbiota composition and claudin-3 expression - YEGEN, BERRAK; AKSU, MEHMET BURAK; AKKİPRİK, MUSTAFA (W B SAUNDERS CO-ELSEVIER INC, 2020)
Background and Purpose: Ongoing high mortality due to necrotizing enterocolitis (NEC) necessitates the investigation of novel treatments to improve the outcome of the affected newborns. The aim was to elucidate the potential therapeutic impact of the nesfatin-1, a peptide with anti-inflammatory and anti-apoptotic effects in several inflammatory processes, on NEC-induced newborn rats. Materials and Methods: Sprague-Dawley pups were separated from their mothers, fed with a hyperosmolar formula and exposed to hypoxia, while control pups had no intervention. NEC-induced pups received saline or nesfatin-1 (0.2 mu g/kg/day) for 3 days, while some nesfatin-1 treated pups were injected with capsaicin (50 mu g/g) for the chemical ablation of afferent neurons. On the 4th day, clinical state and macroscopic gut assessments were made. In intestines, immunohistochemical staining of cycloxygenase-2 (COX-2), nuclear factor (NF)-kappa B-p65 (RelA), vascular endothelial growth factor (VEGF), claudin-3 and zonula occludens-1 (ZO-1) were performed, while gene expressions of COX-2, occludin, claudin-3, NF-kappa B-p65 (RelA) and VEGF were determined using q-PCR. In fecal samples, relative abundance of bacteria was quantified by q-PCR. Biochemical evaluation of oxidant/antioxidant parameters was performed in both intestinal and cerebral tissues. Results: Claudin-3 and ZO-1 immunoreactivity scores were significantly elevated in the nesfatin-1 treated control pups. Nesfatin-1 reduced NEC-induced high macroscopic and clinical scores, inhibited NF-kappa B-65 pathway and maintained the balance of oxidant/antioxidant systems. NEC increased the abundance of Proteobacteria with a concomitant reduction in Actinobacteria and Bacteroidetes, while nesfatin-1 treatment reversed these alterations. Modulatory effects of nesfatin-1 on microbiota and oxidative injury were partially reversed by capsaicin. Immunohistochemistry demonstrated that nesfatin-1 abolished NEC-induced reduction in claudin-3. Gene expressions of COX-2, NF-kappa B, occludin and claudin-3 were elevated in saline-treated NEC pups, while these up-regulated mRNA levels were not further altered in nesfatin-1-treated NEC pups. Conclusion: Nesfatin-1 could be regarded as a potential preventive agent for the treatment of NEC. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Capsaicin-sensitive afferent neurons; Tight junction proteins; Dysbiosis; Oxidative injury; NF-kappa B; TIGHT JUNCTIONS; GROWTH-FACTOR; ACETIC-ACID; MODEL; PATHOGENESIS; INFANTS; GUT; OUTCOMES; STRESS; DAMAGE